2019
DOI: 10.1177/2158244019852482
|View full text |Cite
|
Sign up to set email alerts
|

Place Attachment, Image, and Support for Marijuana Tourism in Colorado

Abstract: Colorado became the first state in the United States that passed the legalization of recreational (retail) marijuana with Amendment 64 in 2012. With this unprecedented tourism environment, it is imperative to understand different perspectives of stakeholders involved. In particular, residents' view is important in that their attitude and behaviors plan and manage the design of marketing activities and sustainable development of the tourist place. Therefore, the purpose of the study is to examine the local resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…Different from some previous studies that regard the concept of residents' support for tourism in terms of attitudes (Nunkoo and So, 2016), this study regards it as residents' PBI, which refers to how much effort residents would exert to support tourism development. In consideration of the importance of residents' support for tourism, many studies have explored the antecedents of such support, including tourism impact (Papastathopoulos et al, 2019), personal benefit (Gursoy et al, 2019), ATT (Ribeiro et al, 2017), state of local economy (Garau-Vadell et al, 2019), emotion (Maruyama et al, 2019) and place attachment (Kang, 2019). Recently, some new variables have been considered to explain residents' support.…”
Section: Residents' Pro-tourism Behavioursmentioning
confidence: 99%
See 1 more Smart Citation
“…Different from some previous studies that regard the concept of residents' support for tourism in terms of attitudes (Nunkoo and So, 2016), this study regards it as residents' PBI, which refers to how much effort residents would exert to support tourism development. In consideration of the importance of residents' support for tourism, many studies have explored the antecedents of such support, including tourism impact (Papastathopoulos et al, 2019), personal benefit (Gursoy et al, 2019), ATT (Ribeiro et al, 2017), state of local economy (Garau-Vadell et al, 2019), emotion (Maruyama et al, 2019) and place attachment (Kang, 2019). Recently, some new variables have been considered to explain residents' support.…”
Section: Residents' Pro-tourism Behavioursmentioning
confidence: 99%
“…In an investigation of 368 residents of Eilat, Stylidis (2018) found that residents with the most favourable image of Eilat tend to support tourism development much more than do the residents with the least favourable image of Eilat. In Colorado, Kang (2019) found that the state image and cannabis image of local residents are both related to their support for marijuana tourism. In a study by Stylidis et al (2014), residents' PI was found to be important in shaping their support for tourism development.…”
Section: Residents' Place Imagementioning
confidence: 99%
“…In the theoretical studies, social exchange theory is the most preferred framework for investigating residents’ attitudes towards tourism development, followed by social representation theory, institutional theory and bottom-up spillover theory (Hadinejad et al , 2019). Overall, whether atheoretical or theoretical, the main purpose of these studies on residents’ BI was to explore the influencing factors, including attitudes towards tourism (Martín et al , 2017; Shen et al , 2019; Ribeiro et al , 2017), perceived impacts (Hammad et al , 2017; Nazneen et al , 2019; Papastathopoulos et al , 2019), local economy and personal benefit (Garau-Vadell et al , 2019; Ribeiro et al , 2017), community satisfaction (Gursoy et al , 2019), emotion (Zheng et al , 2019), image (Kang, 2019) and community participation (Boonsiritomachai and Phonthanukitithaworn, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The effect of cannabis tourism on the overall tourism income was estimated for the Amsterdam metropolitan area 5 and the US state of Colorado (Kang et al, 2016;van Loon, Rouwendal, 2017). The positive economic effect of cannabis tourism in Colorado resulted in the growing support of the locals for this kind of tourism (Kang, Lee, 2018;Kang, 2019). Finally, such cannabis-related events as cannabis festivals and their attendees were characterized from a tourism perspective (Skliamis, Korf, 2019;Kang et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%